P53 independent pathogenic mechanisms contribute to BubR1 microcephaly - Sterling, Noelle A.; Terry, Bethany K.; McDonnell, Julia M.; Kim, Seonhee (Frontiers in Cell and Developmental Biology, 2023)
The mosaic variegated aneuploidy (MVA)-associated gene Budding Uninhibited by Benzimidazole 1B (BUB1B) encodes BUBR1, a core member of the spindle assembly checkpoint complex that ensures kinetochore-spindle attachment for faithful chromosome segregation. BUB1B mutation in humans and its deletion in mice cause microcephaly. In the absence of BubR1 in mice, massive cell death reduces cortical cells during neurogenesis. However, the molecular and cellular mechanisms triggering cell death are unknown. In this study, we performed three-dimensional imaging analysis of mitotic BubR1deficient neural progenitors in a murine model to show profound chromosomal segregation defects and structural abnormalities. Chromosomal defects and accompanying DNA damage result in P53 activation and apoptotic cell death in BubR1 mutants. To test whether the P53 cell death pathway is responsible for cortical cell loss, we co-deleted Trp53 in BubR1-deficient cortices. Remarkably, we discovered that residual apoptotic cell death remains in double mutants lacking P53, suggesting P53independent apoptosis. Furthermore, the minimal rescue of cortical size and cortical neuron numbers in double mutant mice suggests the compelling extent of alternative death mechanisms in the absence of P53. This study demonstrates a potential pathogenic mechanism for microcephaly in MVA patients and uncovers the existence of powerful means of eliminating unfit cells even when the P53 death pathway is disabled.